2017
DOI: 10.1111/jsap.12685
|View full text |Cite|
|
Sign up to set email alerts
|

Long‐term serum bile acid concentrations in 51 dogs after complete extrahepatic congenital portosystemic shunt ligation

Abstract: The results suggest that in dogs treated with complete suture ligation mild increases in serum bile acids are not clinically relevant if there are no physical examination abnormalities, a normal body condition score and no relapse in clinical signs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 28 publications
(34 reference statements)
5
37
0
Order By: Relevance
“…It was recently shown that persistent mild increases in pre-and post-prandial bile acids exist despite resolution of clinical signs in dogs treated for extrahepatic CPSS. 32 However, a relatively large proportion of dogs in the TFB group in our study required revision surgery and this would be considered a failure of the initial surgery. The requirement for routine biochemical follow-up and further surgical intervention in dogs with an apparently good outcome but evidence of persistent shunting remains unclear.…”
Section: Discussionmentioning
confidence: 87%
“…It was recently shown that persistent mild increases in pre-and post-prandial bile acids exist despite resolution of clinical signs in dogs treated for extrahepatic CPSS. 32 However, a relatively large proportion of dogs in the TFB group in our study required revision surgery and this would be considered a failure of the initial surgery. The requirement for routine biochemical follow-up and further surgical intervention in dogs with an apparently good outcome but evidence of persistent shunting remains unclear.…”
Section: Discussionmentioning
confidence: 87%
“…Measurement of fasting blood ammonia concentration is therefore the testing method of choice for diagnosing portosystemic shunting after surgery. An additional ammonia tolerance test or ultrasonography could rule out portosystemic shunting completely . Although also a reliable technique, shunt fractions, using scintigraphy, were not measured in our study because of invasiveness and cost.…”
Section: Discussionmentioning
confidence: 95%
“…The finding of a lack of return to “normal” fits with studies assessing other outcome measures, for example, serum bile acid concentrations have been shown to not return to within reference intervals in the long‐term in the majority of dogs with a complete shunt attenuation (Bristow et al . ). It is suggested that some dogs have continued microvascular shunting following CPSS surgery due to concurrent microvascular dysplasia or primary portal vein hypoplasia (O'Leary et al .…”
Section: Discussionmentioning
confidence: 97%
“…Most studies assessing biochemical parameters as an outcome measure do not show a return to normal reference values (Lawrence et al 1992, Hunt & Hughes , Bristow et al . ), although those assessing owner opinion on outcome do show an apparent return to a “normal” quality of life (QoL). However, for this latter long‐term outcome, most studies use a simple form of owner assessment based on the resolution of clinical signs and whether the dog receives ongoing medical management (Smith et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation